FACTORS AFFECTING BUDGET ABSORPTION OF EXPENDITURE LOCAL APPARATUS ORGANIZATION PRABUMULIH CITY GOVERNMENT DURING THE COVID-19 PERIOD - Kaniya Wardayani; Evada Dewata; Hadi Jauhari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The COVID-19 spread to all countries including Indonesia requires the government to refocus the budget and reallocate activities to accelerate the handling of this outbreak.There are still many local governments in South Sumatra that have not maximized their budget absorption, but on the one hand the Prabumulih Government has a budget absorption that is categorized as good in terms of handling COVID-19, with a percentage of 93.38% in 2019, 93.62% in 2020. This research aims to identify the factors that influence the absorption of the Prabumulih City Government budget which is categorized as high absorption rate with these good criteria. This research was conducted in 37 Local Apparatus Organization Prabumulih Government. The respondents were the Head of Regional Apparatus Organization, Head of Sub-Division of Finance and Commitment Making Officer as many as 90 respondents. The method used is quantitative with primary and secondary data, data collection techniques are through questionnaires and interviews, with uses SPSS version 26. The results show that partially the budget excecution and the process of procurement of goods and services have a significant effect on the high budget absorption of expenditure, while budget planning has no effect on the high absorption of the Prabumulih City Government's.